Short Communication: Genetic variability of local corn cultivars from Kisar Island, Maluku, Indonesia based on morphological characters - HERMALINA SINAY; RITHA L. KARUWAL (Society for Indonesian Biodiversity, 2018)
Sinay H, Karuwal RL. 2018. Short Communication: Genetic variability of local corn cultivars from Kisar Island, Maluku, Indonesia based on morphological characters. Biodiversitas 19: 2302-2307. The purpose of this research is to know the relationship of local corn cultivars derived from Kisar Island based on the morphological characterization. The research was conducted in Kisar Island, Southwest Maluku District, Maluku Province, Indonesia. The morphological characterization was performed on 5 stem characters, 14 leaf characters, 15 male flower characters, 2 female flower characters, 12 cob characters, and 12 seed characters. The description was conducted using the corn descriptor guide by CIMMYT, IBPGR, UPOV, and Departemen Pertanian Republik Indonesia. Color standardization was conducted following standard color charts from the Royal Horticultural Society Color Chart. The data was described and scored based on the appearance of each plant organ observed in the field relative to the descriptor guide. The scoring results were then standardized into 0/1 binary data, which were then analyzed by NTSYS program used for dendrogram construction. Cluster analysis shows that there are two main groups of corn cultivars. The first group consists of merah delima tongkol cokelat, merah darah, putih, kuning genjah, and merah delima tongkol putih. The second group consists of kuning dalam and pulut cultivars.